m6A modification: a novel mechanism that regulates atherosclerosis via macrophage polarization - Li, Xiaying; Zhang, Hengkai; Zhou, Yan; Zhang, Lei; Huang, Ye (Frontiers in Immunology, 2025)
Atherosclerosis is a chronic vascular inflammatory disease in which macrophages play a pivotal role in modulating its pathology. In response to the intraplaque microenvironment, both pro-inflammatory M1 and anti-inflammatory M2 phenotypes of macrophages have the polarization capability, each influencing the inflammatory state through the secretion of distinct cytokines. N6-methyladenosine (m6A) modification, the most prevalent internal chemical modification of RNA, significantly impacts various biological processes, including RNA transcription and protein expression. m6A modification acts as a critical determinant in macrophage polarization, with its molecular mechanisms intricately linked to the progression of atherosclerosis. This review aims to elucidate how different macrophage polarization phenotypes influence the progression of atherosclerosis while also exploring the significance of m6A modifications in this pathological context, thereby providing a theoretical foundation for identifying novel diagnostic and therapeutic targets for atherosclerosis.